Practical actions towards equity in space physics - Liemohn, Michael W. (Frontiers in Astronomy and Space Sciences, 2024)
To mitigate the issues of inequity, exclusion, and a lack of diversity in the solar and space physics research community, a Research Topic collection gathered articles of how scientists in this discipline are taking strides to make this community more welcoming. This review summarizes the key advice from those articles and offers practical actions for both immediate and long-term implementation. There are six major topical categories into which the collection’s article can be grouped: early-year improvements (pre-college and undergraduate); inclusive project teams; diversity in awards; equity in hiring and promotion; leadership development; and the workplace environment. The scope of suggestions ranges from the very localized, such as the language choices we make in everyday conversations, to the institutional, such as the establishment of codes of conduct with a definition and enforcement of consequences for inappropriate behavior regarding inclusion and equity issues. It is hoped that the recommendations are applicable not only to the space physics community but also to others.